Superstition and fantasy in «Gubi Amaya» by Juana Manuela Gorriti - Anchante Arias, Jim Alexander (2022)
This article is an analysis of the story «Gubi Amaya» by the Argentine writer Juana Manuela Gorriti. This analysis is based on the external structure of the story, as well as on the configuration of its represented world, linked to the context of gothic literature and romanticism. From this link, the aim is to demonstrate that the story in question is identified with a fantastic trend from the category of superstition. The theoretical framework used highlights the characterization of the fantastic as a strategy for the revelation of superstitious thought. Thus, a key element to understand this aesthetic-ideological proposal is the recovery of the lost world of childhood by the narrator. This recovery, and the fantastic effect that this entails, is achieved through a space-time journey as a possible key to the enigma in the story. In addition, it expresses in turn a split of the character that gives title to the text, which leads us to the notion of the double as a prototype of fantastic literature. To clarify this paranormal phenomenon, the Freudian concept of the sinister is used, with the objective to clarify whether the action of the narrator in her search for the past is part of reality or the dream world.